Cholinergic-Induced Specific Oscillations in the Medial Prefrontal Cortex to Reverse Propofol Anesthesia - Wang, Lieju; Zhang, Weijie; Wu, Ying; Gao, Yibo; Sun, Na; Ding, Hao; Ren, Jinxuan; Yu, Lina; Wang, Liangliang; Yang, Fen; Xi, Wang; Yan, Min (Frontiers in Neuroscience, 2021)
General anesthesia is a drug-induced reversible condition comprised of altered states of consciousness, amnesia, analgesia and immobility. The medial frontal cortex (mPFC) has been discovered to modulate the level of consciousness through cholinergic and glutamatergic pathways. The optogenetic tools combined with in vivo electrophysiological recording were used to study the neural oscillatory modulation mechanisms in mPFC underlying the loss of consciousness (LOC) and emergence. We found that optogenetic activation of both cholinergic and glutamatergic neurons in the basal forebrain (BF) reversed the hypnotic effect of propofol and accelerated the emergence from propofol-induced unconsciousness. The cholinergic light-activation during propofol anesthesia increased the power in the  (12–20 Hz) and low  (20–30 Hz) bands. Conversely, glutamatergic activation increased the power at less specific broad (1-150 Hz) bands. The cholinergic induced alteration to specific power spectral density (PSD) bands after LOC had opposed effects to that of propofol. These results suggested that the cholinergic system might act on more specific cortical neural circuits related to propofol anesthesia.